From Cyprus to Venice: Art, Exchange and Exile across the Renaissance Mediterranean - Markou, Georgios E. (My University, 2018)
From Cyprus to Venice: Art, Exchange and Exile across the Renaissance Mediterranean
Keywords: Cyprus; Venice; art; exchange; exile; Renaissance Mediterranean